Placing the History of College Writing Stories from the Incomplete Archive - Shepley, Nathan (Open textbook library., 2015)
In Placing the History of College Writing, Nathan Shepley argues that pre-1950s composition history, if analyzed with the right conceptual tools, can pluralize and clarify our understanding of the relationship between the writing of college students and the writing's physical, social, and discursive surroundings. Even if the immediate outcome of student writing is to generate academic credit, Shepley shows, the writing does more complex rhetorical work. It gives students chances to uphold or adjust institutional codes for student behavior, allows students and their literacy sponsors to respond to sociopolitical issues in a city or state, enables faculty and administrators to create strategic representations of institutional or program identities, and connects people across disciplines, occupations, and geographic locations. Shepley argues that even if many of today's composition scholars and instructors work at institutions that lack extensive historical records of the kind usually preferred by composition historians, those scholars and teachers can mine their institutional collections for signs of the various contexts with which student writing dealt.